Realising Decent Academic Citizenship Behaviour in Nigeria’s Higher Education Sector: The Role of Servant Leadership and Psychological Ownership - Aliyu, Mustapha; Maphala, Betty (Acta Universitatis Danubius. Œconomica, 2025)
The study explores the importance of realising decent academic citizenship in Nigeria’s higher education sector with servant leadership and psychological ownership. This has been reported as one of the vacuums that undermines the quality of teaching, research, and community service. Prior evidence has proven the need for a work environment where academics demonstrate a strong sense of belonging. This study was a multidimensional measure based on a survey to analyse the distribution and correlations between respondents’ views of academic staff members employed at Nigerian Federal universities. The cluster sample approach was adopted to arrive at 392 of the population. It was found that servant leaders prioritising welfare significantly promote citizenship behaviour among academics. Similarly, psychological ownership was also found to significantly promote citizenship behaviour toward academics and the university, as academics who feel a sense of belonging are more likely to engage in community service. The implication is that when leaders actively exhibit civic behaviour towards the academics’ welfare and community service, academics are more likely to respond with behaviours that benefit the institutions in reciprocity. This reciprocal interchange will promote a harmonious work environment where workers feel appreciated and are inspired to contribute beyond their official tasks. Moreover, when academics acquire a strong feeling of psychological ownership towards the university, they are more likely to participate in volunteer actions that promote the institution’s vision.